2019
DOI: 10.1111/ijpo.12496
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic obesity susceptibility and mother‐reported eating behaviour in children up to 5 years

Abstract: Summary Background Many genetic polymorphisms identified by genome‐wide association studies for adult body mass index (BMI) have been suggested to regulate food intake. Objective The objective was to study the associations between a genetic obesity risk score, appetitive traits, and growth of children up to age 5 years, with a longitudinal design. Methods In 1142 children from the Etude des Déterminants pre et post natals de la santé de l'ENfant (EDEN) birth cohort, a combined obesity risk‐allele score (BMI ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…As previously described, genotyping candidate single nucleotide polymorphisms (SNPs) was conducted at the Medical Research Council Epidemiology Unit, Cambridge (iPLEX platform; Sequenom) [ 40 ]. Among the 32 loci identified by Speliotes et al as having genome-wide significant associations with BMI in adults [ 41 ], in the present study, we considered the 16 SNPs also showing associations with childhood BMI in that original report [ 41 ] or in subsequent data [ 42 ], as in previous studies [ 6 ]. Briefly, a combined obesity risk-allele score, indicating genetic susceptibility to obesity (BMI-GRS), was calculated for each included infant as the sum of risk alleles (0, 1 or 2) associated with higher BMI across the 16 SNPs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously described, genotyping candidate single nucleotide polymorphisms (SNPs) was conducted at the Medical Research Council Epidemiology Unit, Cambridge (iPLEX platform; Sequenom) [ 40 ]. Among the 32 loci identified by Speliotes et al as having genome-wide significant associations with BMI in adults [ 41 ], in the present study, we considered the 16 SNPs also showing associations with childhood BMI in that original report [ 41 ] or in subsequent data [ 42 ], as in previous studies [ 6 ]. Briefly, a combined obesity risk-allele score, indicating genetic susceptibility to obesity (BMI-GRS), was calculated for each included infant as the sum of risk alleles (0, 1 or 2) associated with higher BMI across the 16 SNPs.…”
Section: Methodsmentioning
confidence: 99%
“…A great number of the genes identified by genome-wide association study of obesity and also those from studies of monogenic forms of severe childhood obesity appear to be involved in the central regulation of food intake [ 5 ]. Moreover, several studies have shown that genetic susceptibility to obesity affects infant [ 6 ] and child’s appetite [ 4 , 7 ] and that early appetite is related to the child’s weight status later in childhood [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated above, feelings of hunger or feeling over-full both might affect children’s ability to process information in a manner conducive to learning. Eating in the absence of hunger, or overeating [29], is a contributor to excess body fat and childhood obesity [30]. Studies aimed at understanding the relationship between obesity and cognition during childhood have only recently emerged, and the majority of findings have been limited to the domain of executive control [31,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…63,64 Another recent study has reported that genetic susceptibility to develop overweight and obesity might be correlated with appetitive traits in children, which therefore might benefit from family counselling. 65 This result stresses the tight relationship between the genetic component and the environment, with a close and reciprocal influence. For this reason, although the genetic patrimony cannot be directly influenced, it is important to stress the role of healthy behaviours in the family, in order to try to at least partially counteract inherited genetic traits that increase the risk of developing ASCVD risk factors.…”
Section: Primordial Preventionmentioning
confidence: 77%